ANALISIS STRATEGI PENGEMBANGAN PEMBANGKIT LISTRIK WILAYAH KALIMANTAN BARAT GUNA MENDUKUNG PERTAHANAN NEGARA REPUBLIK INDONESIA - Nugroho, Fajar Bayu; Murtiana, Sri; Pahlevi, Rinaldi; B Z, Cahya Maharani (AUSTENIT, 2024)
West Kalimantan is one of the Indonesian provinces that borders directly with other countries. West Kalimantan on the country map directly borders Sarawak in East Malaysia. This status makes West Kalimantan a province that has official land access to other countries. Import of electricity from Malaysia is still ongoing to meet the need electricity in West Kalimantan which is prone to national security threats. This study to analyze strategy of power plant development in the West Kalimantan (Kalbar) region which is on an island directly adjacent to Malaysia, in order to support energy independence and national defense. Data sources of this research from journals, books, previous research, scientific articles and news from official websites. There is a need for a power plant development strategy in the West Kalimantan region to support national defense. Coordination related to the development of power plants will support the ability and strength of the defense sector towards national security, both when there is a threat or the country is at peace.